Position paper: Rapid responses to steroids: current status and future prospects - Wendler, Alexandra; Baldi, Elisabetta; Harvey, Brian J; Nadal, Angel; Norman, Anthony; Wehling, Martin (European journal of endocrinology, 2010)
Steroids exert their actions through several pathways. The classical genomic pathway, which involves binding of steroids to receptors and subsequent modulation of gene expression, is well characterized. Besides this, rapid actions of steroids have been shown to exist. Since 30 years, research on rapid actions of steroids is an emerging field of science. Today, rapid effects of steroids are well established, and are shown to exist for every type of steroid. The classical steroid receptors have been shown to be involved in rapid actions, but there is also strong evidence that unrelated structures mediate these rapid effects. Despite increasing knowledge about the mechanisms and structures which mediate these actions, there is still no unanimous acceptance of this category. This article briefly reviews the history of the field including current controversies and challenges. It is not meant as a broad review of literature, but should increase the awareness of the endocrinology society for rapid responses to steroids. As members of the organizing committee of the VI International Meeting on Rapid Responses to Steroid Hormones 2009, we propose a research agenda focusing on the identification of new receptoral structures and the identification of mechanisms of actions at physiological steroid concentrations. Additionally, efforts for the propagation of translational studies, which should finally lead to clinical benefit in the area of rapid steroid action research, should be intensified.
Gesehen am 03.11.2023